Is This All There Is? : On Resurrection and Eternal Life - Lohfink, Gerhard, 1934- (Book collections on Project MUSE., 2018)
"Is the Christian hope for resurrection still alive or has it become tired? How can we talk about the Resurrection today? Gerhard Lohfink takes up the question of death and resurrection in this new book. He argues against the dazzling array of today's ideas and expectations and seeks his answers in Scripture, the Christian tradition, and human reason. With his characteristically gentle but clear language, he reveals the power of Christian resurrection, showing it is not about events that lie in the distant future but rather occurrences incomprehensively close to us. They were long since begun and they will embrace us fully in our own death."--Amazon.com.